Crystal Structure of Nonaaquayttrium(III) Bromate at 100 K - Alireza Abbasi (Iranian Journal of Chemistry & Chemical Engineering, 2007)
The structure of the nonaaquayttrium (III) bromate, [Y(H2O)9](BrO3)3, at low temperature (100 K) has been studied by means of single-crystal X-ray diffraction. Crystallography shows a hexagonal unit cell, space group P63/mmc (No. 194) with Z = 2, a = b = 11.7104(11) Å, c = 6.6259(5) Å and V = 786.90(12) Å3 at 100 K. The hydrated trivalent yttrium(III) ion forms a tricapped trigonal prism, in which the yttrium(III) ion is surrounded by six equidistant water molecules in the prism and three more distant water molecules in capping positions with M-O bond distances of 2.370(2) and 2.446(3) Å, respectively. Relatively strong hydrogen bonds (2.818 and 2.851 Å) from water molecules to the bromate ions stabilize the trigonal prism around the yttrium(III) ions.